Pengaruh Pelayanan Klinik Sanitasi dengan Metode Penyuluhan Terhadap Kualitas Lingkungan Rumah Balita Penderita ISPA di Wilayah Kerja Puskesmas Gamping I Sleman 2010 - Setiana SetiAna; Yamtana Yamtana; Achmad Husein (Sanitasi: Jurnal Kesehatan Lingkungan, 2010)
Acute Respiratory Infection (ARI) is an environmental-based disease that still a common problem of public health in Indonesia. One of the available services in Health Centers is Sanitation Clinic. The existence of sanitation clinic in Gam-ping I Health Center, Sleman, Yogyakarta, has never been evaluated. One of the currently working activities of the sanitation clinic is elucidation. The object-ive of the study is to find out the effects of sanitation clinic services with elu-cidative method on the quality of home environment of ARI patients of under five children at the working area of Gamping I Health Center, Sleman, Yogya-karta. It is a quasi experimental study with one group pre test and post test design. The number of samples was 20 ARI patient recorded on April 2010. Respondents of the study were their mothers or attendants and the objects were bedrooms. Independent variable of the study is sanitation clinic services with elucidative method, meanwhile the dependent variables is the quality of home environment which consists of temperature, humidity, illumination, dust concentration, and air microbe number. The results of measurement were analyzed descriptively and analytically. Analytically, the data were tested with SPSS 15.0 for windows in which dependent t-test and chi-square found the p-value for each parameter are < 0.05; therefore it can be interpreted that there is a difference in the quality of home environment before and after receiving the treatment. It is suggested that the health providers at the sanitation clinic to more intensively monitor and provide elucidation to mothers or attendants of ARI patients of under five children in their working area.